Optimizing patient involvement in quality improvement - Armstrong, Natalie (John Wiley and Sons Inc., 2013)
INTRODUCTION: Patient and public involvement in healthcare planning, service development and health‐related research has received significant attention. However, evidence about the role of patient involvement in quality improvement work is more limited. We aimed to characterize patient involvement in three improvement projects and to identify strengths and weaknesses of contrasting approaches. METHODS: Three case study quality improvement projects were purposively sampled from a broader programme. We used an ethnographic approach involving 126 in‐depth interviews, 12 weeks of non‐participant observations and documentary analysis. Data analysis was based on the constant comparative method. RESULTS: The three projects differed in the ways they involved patients in their quality improvement work, including their rationales for including patients. We characterized three very different models of patient involvement, which were each influenced by project context. Patients played distinctive roles across the three projects, acting in some cases as intermediaries between the wider patient community and clinicians, and sometimes undertaking persuasive work to convince clinicians of the need for change. We identified specific strategies that can be used to help ensure that patient involvement works most effectively and that the enthusiasm of patients to make a difference is not dissipated. CONCLUSION: Patient involvement in quality improvement work needs careful management to realize its full potential.